Relationship lending and monetary policy pass-through - Jin Cao; Pierre Dubuis; Karolis Liaudinskas (Norges Bank, 2025)
This paper investigates the link between bank-firm lending relationships and monetary policy pass-through, focusing on episodes of low interest rates. Using administrative tax and bank supervisory data ranging from 1997 to 2019, we track the entirety of bank-firm relationships in Norway. Our analysis shows that when the central bank's policy rate is relatively low, firms that have maintained a long-term relationship with their bank experience a lower pass-through of further policy rate cuts. Specifically, we find that when the policy rate is 1.09%, each additional year of relationship decreases the pass-through of a rate cut by 2.7 percentage points. We propose a theoretical model to rationalize our empirical findings, where state-dependent differential pass-through results from the presence of firms' switching costs and banks' leverage constraint. The model highlights that the composition of relationship lengths in the economy matters for aggregate monetary policy pass-through. The proportion of long-term relationships in the Norwegian economy significantly increased after the global financial crisis. Using the model, we calculate a counterfactual aggregate pass-through for 2017, a period of monetary easing in a low-rate environment, assuming this proportion had remained at its pre-crisis level. Our findings indicate a substantial increase in aggregate pass-through, on the order of 20%.
hdl:11250/3179224
Keywords: G21; E58; E52; E43; E50; 330; Relationship lending; Monetary policy pass-through; Low interest rates; Policy rate; Switching costs